Dynamic Shadow Pricing of Electricity under Renewable Surplus: Evidence from a Regulated Power System - Gammanpila, W. D.; Gammanpila, A. C.; Kularathna, A.H.T.S.; Jayasooriya, N.K. (International Journal of Energy Economics and Policy, 2026)
Many regulated electricity systems operate without real-time market pricing, relying instead on administratively determined tariffs that fail to reflect short-run scarcity and surplus conditions. As variable renewable energy penetration increases, temporal mismatches between generation and demand create recurring periods of surplus and tightness within the same day, leading to renewable curtailment, inefficient dispatch, and underutilisation of storage and demand-side flexibility. This paper develops a deterministic shadow-pricing framework that infers the marginal value of electricity directly from observable system conditions rather than market-clearing prices. Using realised solar, wind, and demand data, we construct a dynamic proxy for the shadow price based on the relaxation or tightening of the short-run energy balance constraint. The resulting signal captures continuous variation in system scarcity and reveals economically meaningful price spreads that persist even under regulated dispatch. Empirical evidence from Sri Lanka shows that renewable surplus systematically depresses implied marginal value, while evening demand peaks restore scarcity, creating predictable windows for storage arbitrage and flexible demand. The framework provides a practical, low-complexity mechanism for improving operational efficiency, investment decisions, and tariff design in renewable-rich systems without requiring wholesale market reform.